Secondary metabolites, letalithy and antimicrobial activity of six marine sponges from Mochima Bay, Sucre state, Venezuela. (UNED Research Journal, 2015)
he specimens of the sponges Aplysina lacunosa, Aplysina fulva, Cliona varians, Cinachyrella kuekenthali, Amphimedon viridis and Aaptos pernucleata, were collected in Mochima Bay, Venezuela, in October 2009 with the purpose of identifying families of secondary metabolites and evaluating the antibacterial properties, antifungal and brine shrimp lethal study of the ethyl acetate soluble fractions of these sponges. The chemical evaluation showed the presence of alkaloids, sterols, triterpenes, methylene ketone and tannins. The ethyl acetate soluble fractions of A. pernucleata, A. fulva and A. lacunosa sponges were the only ones that showed antibacterial activity against Staphylococcus aureus, Listeria monocytogenes, and Escherichia coli; the soluble fraction of A. lacunosa showed the highest inhibition zones. The antifungal activity was not significant, except for A. pernucleata sponge wich showed mild activity against Candida albicans. The most prominent lethal activity in Artemia salina, were observed for C. kuekenthali, A. viridis and A. pernucleata sponges, with LC50 values of 4,10, 1,13 and < 0,01µg/mL respectively. These results allow profiling the sponges A. lacunosa, A. pernucleata and A. fulva as promising sources of antimicrobial compounds and the sponges C. kuekenthali, A. viridis and A. pernucleata as sources of antitumor compounds.
Keywords: chemical evaluation; secondary metabolites; antimicrobial activity; Artemia salina; lethality; sponges.